Interacción sísmica suelo-estructura en edificaciones con muros de ductilidad limitada sobre plateas de cimentación - Cerna Vasquez, Marco Antonio (2021)
This investigation is directed to the calculation of buildings with limited ductility walls, considering of the base foundation flexibility, known worldwide as soil- structure interaction. For the development of this research, we manage different models proposed by different researches in the matter of Structural and Geotechnical Engineering. The soil-structure interaction models studied in this research, were based in different researches published by Ph.D. Genner Villarreal Castro, which reflected extensive knowledge and theories about this area of seismic investigation, taking main consideration that the structures must have the required knowledge of the country. In this investigation development, the most competent dynamic models on plates foundation were chosen, considering the flexibility and the physical – mechanical properties of soil. Similarly developed a building modeling methodology was developed with ductility walls on foundation plates in front of seismic action with various angles of inclination and under conditions of Peru , according to requirements of the seismic design standard E030. Finally, the analysis and structural design of the study building were done. In these topics, different points were developed. Such a structural requirements, stiffness and mass center seismic analysis of the building, criteria of structural